Ecosystem Modifications (1956-2014) in Lake Victoria (East Africa): A Review - Gophen, Moshe (Archives of Business Research, 2019)
A brief historical (1956-2014) review of the Lake Victoria ecological development is presented. The Lake Victoria ecosystem structure was thoroughly modified after the invasion of the predator fish Lates niloticus (Nile perch). The relative capacity and functional activity of the food-web compartments was quantitative and qualitative altered. The trophic status of Lake Victoria ecosystem was shifted toward eutrophication : phytoplankton species composition and densities were modified, fish assemblages were converted from about 400 Haplochromine species diversity to large body predator , Nile perch dominance. Consequently , the fishery was changed accompanied by Socio-Economic consequences. The thermal structure trait shifted towards enhancement of anoxia and Hypolimnetic volume extension.